Selective Ammonia Electrooxidation on RuO2: Competitive and Synergistic Interplay between Ammonia and Hydroxide - Chen, Sijie; Zhang, Ting; Zheng, Ling; Gao, Jinghao; Huang, Xiaowu; Gu, Jun; Vogt, Charlotte; Zheng, Weiran (Journal of physical chemistry. C, 2025)
Ammonia electrooxidation (AOR) on metal oxides involves a complex interplay between nitrogen (N)- and oxygen (O)-containing intermediates, critically influencing reaction activity and product selectivity. In this study, we investigate AOR on RuO2 under alkaline conditions with electrochemical and in situ characterization techniques, including differential electrochemical mass spectrometry (DEMS) and ultraviolet–visible (UV–vis) spectroelectrochemistry. The effects of NH3 and OH– concentration (0.1–2.0 M, and 0.01–1.0 M, respectively) as well as applied potential on AOR and the concurrent oxygen evolution reaction (OER) are examined. NO and NO3 – are identified as the main AOR products, especially at high OH– concentration and potential, with minor quantities of N2O and no detectable N2 formation. Increasing NH3 concentration suppresses OER by competing for surface sites, particularly at low OH– concentrations, while promoting AOR pathways. Product analysis with DEMS and colorimetry identifies two distinct regimes of N2O and NO3 – formation: a low-potential, NH3-driven pathway, and a high-potential, *OOH-mediated pathway. The exclusive formation of NO at high OH– concentration and potential underscores the role of *OOH in *NOH dehydrogenation. Moreover, NO3 – arises through both *OOH-assisted and NH3-rich surface mechanisms, depending on the electrolyte environment. The absence of N2 suggests that *N–*N coupling is kinetically or thermodynamically limited on RuO2. These findings highlight the critical role of intermediates (*NH x , *NOH, and *OOH) in dictating product selectivity, offering tunable control over AOR pathways.